Do orientation programs help new graduates?. (January 2016) - Strauss, Ester; Ovnat, Chaya; Gonen, Ayala; Lev-Ari, Lilac; Mizrahi, Ayala
Summary: Background: There is a need for effective orientation programs that are designed to prepare new graduate nurses in providing safe, competent, and effective patient care. However, little is known regarding the overall effectiveness of these programs for nursing graduates. Objectives: To determine whether the transition of the graduates into their working place included a structured orientation program, and to assess the effectiveness of the program from the graduate's perspective. Design: Cross-sectional survey design. Settings, Participants, and Methods: Data were collected from four different institutions in Israel. A questionnaire was divided among 100 graduate nurses and had a response rate of 79%. A questionnaire was designed and included closed and open questions. It was evaluated for internal consistency by standardized Cronbach's alpha coefficients (Cronbach's alpha was between 0.91 and 0.96). Results: Only 50.6% of the nurses in the sample reported having a structured orientation program. We found positive significant correlations between having a structured orientation program to adaptation of the graduate nurses to the ward, satisfaction of the graduates on the ward. Positive correlations were also found between support that the graduates received to their satisfaction on the ward. Retention on the ward was highly correlated with having a program, satisfaction, adaptation, and support. We found differences in acclimation indices by religiosity. Conclusions: Different delivery approaches of orientation programs may determine satisfaction of the graduates. A transition program which overlooks individual needs or an informal individual approach may lead to dissatisfaction. A program which is "tailored" to the graduate, by an assigned one-to-one appointment of a preceptor, may lead to satisfaction, which in turn may assure an ongoing supply of competent RNs who will remain in those settings. Highlights: 76% of the nurses in the sample reported having a structured orientation program. We found positive significant correlations between having a structured orientation program to adaptation of the graduate nurses to the ward, satisfaction of the graduates on the ward. Positive correlations were also found between support that the graduates received to their satisfaction on the ward. Retention on the ward was highly correlated with having a program, satisfaction, adaptation, and support. We found differences in acclimation indices by religiosity.